Perbandingan Sistem Pendaftaran Indikasi Geografis Di European Union dan Asean Serta Implikasi Hukum Terhadap Indonesia - Medina, Dayu (Faculty of Law, Andalas University, 2023)
Protection of Geographical Indications (GI) is contained in The Trade Related Aspects of Intellectual Property Rights (TRIPs), GI is also regulated in other international agreements, such as the Paris Convention, Madrid Agreement, and Lisbon Agreement. In the provisions of TRIPs, the regulation of GI protection is left to each country to regulate it according to their needs and capabilities, TRIPs is only a minimum standard in protection. Thus countries regulate GI according to their needs. However, on the one hand, regarding the registration of GI, a broader mechanism is needed so that GI can be protected internationally. The European Union (EU) and ASEAN have regional/international GI registration mechanisms. This study analyzes the GI registration system through the EU and ASEAN mechanisms and then the legal implications for Indonesia. The method used is normative juridical using secondary data. The system for registration of GIs through the EU and ASEAN mechanisms does not differ much, only the EU regulates GIs that can be registered more broadly and in detail, meanwhile, ASEAN has not regulated the scope of GIs. In addition, the EU has a clear mechanism (starting from registration, opposition (objections), and time of submission, etc.), meanwhile, ASEAN has not regulated in detail like the EU. The legal implications for Indonesian GIs are that Indonesia fixes the laws and regulations related to GIs, and registers Indonesian GIs with the EU and ASEAN.